Treatment of congenital hip dislocation before the walking age - Daniele Sini; Federica De Rosa; Carlo Origo (PAGEPress Publications, 2022)
The worst type of hip developmental dysplasia, known as congenital hip dislocation (CHD), is characterized by acetabular cavity, proximal femoral segment, and ligamentus capsule apparatus dysmorphisms that result in partial or total loss of the hip joint's relationship. We provide the following example: Hip dislocation has been diagnosed in a male infant 2 months old. The patient underwent progressive abduction followed by longitudinal skin traction using the Morel technique. After performing an artrography on the hip while under general anesthesia, which revealed a reducible and stable hip, we continued with spica cast immobilization in a human position. To promote proper joint development, improve standing posture, enhance gait, and correct pelvic and spinal imbalances, the treatment aims to reduce joint dislocation and rebuild joint relationships. To gradually clean the structures and lower the risk of distant avascular necrosis (AVN) of the femoral head development, slow and gradual traction is applied to Morel's bed.